Clinical significance of Glutamate Dehydrogenase 2, Sirtuin 4 and some Electrolyte-Trace Elements in Epileptic patient : Clinical significance of enzymes and some Electrolyte-Trace Elements in Epileptic patient - Ahmed, Snowber M.; Ali, Zeyan A. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2026)
Epilepsy is a neurological condition that is caused by an imbalance of excitation and inhibition in the brain. Many factors influence this imbalance, including enzymes involved in producing neurotransmitters, the balance of electrolytes, and the effect of trace elements. Thus, this study aimed to investigate the levels of glutamate dehydrogenase 2 (GDH2), NAD-dependent ADP-ribosyl transferase sirtuin 4 (SIRT4), electrolytes (Na, K, and Cl), and trace elements (Zn, Cu, and Se) in epileptic patients and compare them with control groups. The blood serum from 30 focal epilepsy (FE) patients, 30 generalized epilepsy (GE) patients, and 30 control groups was collected in Erbil City Hospital. The results of the study showed a significant decrease in GDH2 with a P < 0.0001 for the FE and GE groups. SIRT4 levels were significantly increased in both groups, compared to the control group. Furthermore, levels of Na, Zn, and Se were markedly reduced, while no significant variations were observed in K, Cl, and Cu levels between epileptic patients and control groups. The ROC curve and area under the curve (AUC) results for GDH2 (0.8092), SIRT4 (0.8956), sodium (0.8673), zinc (0.9711), and selenium (1). The results of the artificial neural networks showed that selenium, zinc, sodium, GDH2, and SIRT4 had the greatest impact on how the network classified patients as having epilepsy or being healthy. The results of GDH2, SIRT4, Na, Zn, and Se may be utilized as parameters for detecting the state of epileptic patients and used as beneficial biomarkers